2016
DOI: 10.1161/hypertensionaha.116.08184
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotaline-Induced Pulmonary Hypertension Involves Downregulation of Antiaging Protein Klotho and eNOS Activity

Abstract: The objective of this study is to investigate whether stem cell delivery of secreted Klotho (SKL), an aging-suppressor protein, attenuates monocrotaline (MCT)-induced pulmonary vascular dysfunction and remodelling. Overexpression of SKL in mesenchymal stem cells (MSCs) was achieved by transfecting MSCs with lentiviral vectors expressing SKL-GFP. Four groups of rats were treated with MCT, while an additional group was given saline (control). Three days later, four MCT-treated groups received IV delivery of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
5
21
0
Order By: Relevance
“…Recently, it has been reported that the reduction of Klotho protein, which is an anti-aging protein, is involved in the reduction of NOS of the pulmonary artery in monocrotaline-induced pulmonary hypertension rats. 36) These results, including ours, suggest that anti-aging proteins regulate eNOS bioavailability, and affect the pathogenesis of pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, it has been reported that the reduction of Klotho protein, which is an anti-aging protein, is involved in the reduction of NOS of the pulmonary artery in monocrotaline-induced pulmonary hypertension rats. 36) These results, including ours, suggest that anti-aging proteins regulate eNOS bioavailability, and affect the pathogenesis of pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…The histological and IHC analysis was performed as described in our recent studies (Chen, Lin & Sun, 2016; Gao etĀ al., 2016; Lin, Chen & Sun, 2016; Lin & Sun, 2015a,b; Varshney, Ali, Wu & Sun, 2016). For details, see Data S1.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the authors demonstrated in the same experiment that the addition of soluble klotho without FGF23 to mouse aorta rings induced vasoconstriction and the production of ROS. The increase in endothelial NO following soluble klotho administration could explain the antagonistic effects of klotho to monocrotalineinduced experimental PAH in murine models (12). However, the evaluation of soluble a-klotho in the peripheral blood from 64 precapillary PAH patients did not find a significant association with haemodynamic findings (13).…”
Section: Original Papermentioning
confidence: 99%